Biosorption of Chromium and Nickel from Industrial Oil Mill Wastewater Using Groundnut Pod Waste Activated Carbon - Nanret Liba Yaceh; Michael Sunday Olakunle; Nehemiah Samuel Maina (ABUAD Journal of Engineering Research and Development)
Groundnut shell activated carbon was developed and characterized by chemical activation using phosphoric acid (H3PO4) for the uptake of Cr and Ni in a batch biosorption process. The purpose of this study was to reduce the spread of heavy metals in industrial oil mill wastewater. In this study characterization of activated carbon using, surface chemistry (FTI-IR), surface area (BET), surface morphology, and elemental identification (SEM/EDX) were all carried out, and the BET surface area was 689.41 m2/g for groundnut shell activated carbon. This study was also executed to determine the optimum biosorption efficiency parameters for Cr and Ni removal using Response Surface Methodology (RSM) to obtain maximum biosorption efficiency. The factors considered were temperature (25-55oC), adsorbent dosage (1-3 g) and contact time (1-2 hrs). Biosorption efficiency was the response. ANOVA analysis was carried out to analyse the most effective factor in experimental design response. The optimum conditions for removal of Cr and Ni were adsorbent dosage 0.40 g, contact time 1.1 hr and temperature 42.02 oC, which shows the maximum biosorption efficiency of 97.1% for Cr removal and 94.8% for Ni removal. Isotherm models analyses showed that the biosorption process was best fitted to Langmuir model and was physical. Results of the kinetic studies and thermodynamic parameters revealed that the biosorption process followed a pseudo-second-order, endothermic, and spontaneous in nature.